2023
DOI: 10.1002/smll.202207808
|View full text |Cite
|
Sign up to set email alerts
|

Promoting CO2Dynamic Activation via Micro‐Engineering Technology for Enhancing Electrochemical CO2Reduction

Abstract: Optimizing the coordination structure and microscopic reaction environment of isolated metal sites is promising for boosting catalytic activity for electrocatalytic CO2 reduction reaction (CO2RR) but is still challenging to achieve. Herein, a newly electrostatic induced self‐assembly strategy for encapsulating isolated Ni‐C3N1 moiety into hollow nano‐reactor as I‐Ni SA/NHCRs is developed, which achieves FECO of 94.91% at −0.80 V, the CO partial current density of ≈−15.35 mA cm−2, superior to that with outer Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Nevertheless, the discharge current density in the Zn–CO 2 battery is significantly lower compared to the current density of eCO 2 RR in the flow cell, similar to existing literature. 48,49 The LSV curves of anodic Zn oxidation of the Zn plate in 6 M KOH solution confirm the negligible effect of the Zn anode in current density (Fig. S23, ESI†).…”
Section: Resultsmentioning
confidence: 69%
“…Nevertheless, the discharge current density in the Zn–CO 2 battery is significantly lower compared to the current density of eCO 2 RR in the flow cell, similar to existing literature. 48,49 The LSV curves of anodic Zn oxidation of the Zn plate in 6 M KOH solution confirm the negligible effect of the Zn anode in current density (Fig. S23, ESI†).…”
Section: Resultsmentioning
confidence: 69%
“…This result further proves that an optimized hierarchical porous structure is helpful for exposing more active sites and mass transport, thus facilitating CO 2 reduction kinetics. By contrast, with the further increase of overpotential, the ultrahigh slope suggests that the desorption of *CO also has an effect on the reaction kinetics of ECO2RR due to the insufficient CO 2 supply . In addition, the ECSA was estimated (Figures S12–S13), and to our observation, Ni@MicroPNC possesses the highest double layer capacity ( C dl ) value of 16.5 mF, which is much higher than Ni@MesoPNC (12.2 mF), MicroPNC (8.3 mF), and NC (1.27 mF).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Goyal et al suggested that enhanced roughness on a nanoporous Au-catalyst resulted in an increase in availability of active sites . In addition, Fu and Yang et al identified that enhanced CO 2 reduction performances could be determined not only by the heteroatom doping level and heteroatom doping configuration but also by the porous architecture. , Moreover, Gong et al reported facilitated CO 2 diffusion in a hollow nanoreactor with rich active sites, which resulted in enhanced electrochemical CO 2 reduction performances consequently . Inspired by all this information and also by our own interest in designing a robust electrocatalyst for ECO2RR, we became interested in providing plentiful active sites by regulating porous architectures of catalysts in ECO2RR .…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, the researchers of the same group rationally developed a novel catalyst consisting of Ni-C 3 N 1 moiety confined in hollow carbon reactors (I-Ni SA/NHCRs), which was reported to achieve a high FE CO of 94.91% at −0.80 V in H-cell, and showing higher CO partial current density (−15.35 mA cm −2 ) than that with outer Ni-C 2 N 2 moiety (O–Ni SA/NHCRs, −12.06 mA cm −2 ), or without hollow structure (Ni-NC, −5.39 mA cm −2 ). 147 More importantly, a high FE CO of up to 98.41% was achieved for I-Ni SA/NHCRs at 100 mA cm −2 in a flow cell with 1 M KHCO 3 electrolyte, implying a huge potential for practical application. It was proposed, based on COMSOL multiphysics finite element simulations, that the diffusion time of CO 2 molecules in hollow nano-reactor structure (model II, I-Ni SA/NHCRs-based electrode) (CO 2 diffusion time, ∼1.25 s) is much faster than that of solid sphere structure (model I, Ni-NC-based electrode) (CO 2 diffusion time, >2.0 s) ( Fig.…”
Section: Electrocatalytic Co 2 Conversion Of Hollo...mentioning
confidence: 97%